Ecosystem-based management of coral reefs from afar – A guide for remote scientists and remote places. Issue 139 (January 2023) - Cowburn, Benjamin; Alliji, Khatija; Bluemel, Joanna K.; Couce, Elena; Lawrance, Emma; McManus, Edmund; van Hoytema, Nanne; Devlin, Michelle
Abstract: Modern-day coral reef conservation requires connections between researchers, decision-makers and stakeholders to achieve holistic ecosystem-based management (EBM), rooted in and supported by local communities. However, the COVID-19 pandemic, global political and financial instability and growing concerns over emissions from air travel have meant that face-to-face meetings and in-person fieldwork are increasingly difficult for many researchers at distant institutions. In this paper we discuss how to achieve EBM remotely, using a combination of freely available online data, remote fieldwork techniques and virtual communication and engagement tools. We highlight resources that have been useful in our work for components of overseas EBM and discuss lessons learned from those experiences. There are benefits to remote working, including reduced carbon emissions and travel costs, the ability to record and re-use electronic training materials, the ability to reach a wider audience than through face-to-face meetings and an increased reliance and division of labour with local researchers and stakeholders. However, developing new relationships and gaining a deeper contextual understanding of the local site and culture is not easily replaced by online or remote methods. Post-COVID-19, it is likely that some aspects of remote working within coral reef conservation will continue, as in many other aspects of global collaboration. We propose a blended approach where much of the work and collaboration is conducted online, but with some in-person visits to develop the key relationships or decisions are needed.